Desıgn and Manufacture of Graphıc Desıgn & Motıon Graphıc at Coffee Shop Aftertaste - Tony Wibowo; Ericson Hermanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
In this article, we will discuss the design and manufacture of graphic & motion graphic designs, in a medium, small, micro-business (MSME) in the city of Batam called coffee shop aftertaste. The purpose of this scientific project is to promote brand image through digital media because there is not enough promotion in coffee shop Aftertaste digital media so that it is still not well known among the wider community. Therefore, the author decided to make graphic & motion graphic designs in the form of videos, posters, character designs, and also coupon designs using the Multimedia Development Life Cycle (MDLC) method. The result of this scientific project is an increase in popularity and the introduction of branding through Instagram stories